POTENSI KULINER LOKAL DALAM MENARIK KEDATANGAN WISATAWAN DI PULAU LOMBOK - Putra, I Gusti Bagus Wira; Wirawan, Komang Satria; Rai, Ida Ayu Ketut; Maharani, Ni Kadek Ajeng; Dewi, Ni Putu Sasmika (Institut Agama Hindu Negeri Gde Puda Mataram, 2024)
The aim of preparing the article is to analyze the potential of local culinary delights in attracting tourists to Lombok Island. This study is an initial study using qualitative research using the literature study method. The data collection used is observation, interviews and documentation from various types of literature such as books, journals and other print media. Based on the results of studies conducted, there are several local culinary potentials from areas in Lombok, namely Central Lombok (Nasi Puyung), North Lombok (Sate Tanjung), West Lombok (Pelecing Kangkung and Sate Bulayak), East Lombok (Sayur Ares), and Mataram City (Taliwang Chicken and Rembiga Sate). Based on this potential, it is hoped that the people of Lombok will continue to maintain and preserve local culinary or traditional food. And can promote it to tourists.